BRCA, the Oviduct, and the Space and Time Continuum of Pelvic Serous Carcinogenesis. (1st May 2012) - Crum, Christopher P.; McKeon, Frank D.; Xian, Wa
Abstract : Abstract: In recent years, the distal oviduct has emerged as a critical organ in the pathogenesis of pelvic ("ovarian") serous cancer. Studies have uncovered early serous tubal intraepithelial carcinomas in approximately 8% of asymptomatic women with germline BRCA1 or BRCA2 mutations, linked serous tubal intraepithelial carcinomas to one half of serous cancers irrespective of genetic risk, and described a precursor lesion in the distal tube with early alterations in p53 function (the p53 signature). This work has established a linear serous carcinogenic sequence in a single focus within the fimbria. In addition, a more broadly distributed array of gene alterations has been discovered in the oviduct, manifested as secretory (or stem) cell outgrowths that are increased in frequency as a function of older age and serous cancer status. These "surrogate precursors" expand the existing model beyond the fimbria, implying that the molecular events leading to serous cancer are distributed over space and time. The potential promise of these discoveries is "targeted prevention" by discovering of multiple pathways integral to carcinogenesis and successfully preventing malignancy by interrupting one or a few of these pathways.